Down‐regulation of BDNF in cell and animal models increases striatal‐enriched protein tyrosine phosphatase 61 (STEP61) levels. Issue 2 (17th September 2015) - Xu, Jian; Kurup, Pradeep; Azkona, Garikoitz; Baguley, Tyler D.; Saavedra, Ana; Nairn, Angus C.; Ellman, Jonathan A.; Pérez‐Navarro, Esther; Lombroso, Paul J.
Abstract: Brain‐derived neurotrophic factor (BDNF) regulates synaptic strengthening and memory consolidation, and altered BDNF expression is implicated in a number of neuropsychiatric and neurodegenerative disorders. BDNF potentiates N ‐methyl‐D‐aspartate receptor function through activation of Fyn and ERK1/2. STriatal‐Enriched protein tyrosine Phosphatase (STEP) is also implicated in many of the same disorders as BDNF but, in contrast to BDNF, STEP opposes the development of synaptic strengthening. STEP‐mediated dephosphorylation of the NMDA receptor subunit GluN2B promotes internalization of GluN2B‐containing NMDA receptors, while dephosphorylation of the kinases Fyn, Pyk2, and ERK1/2 leads to their inactivation. Thus, STEP and BDNF have opposing functions. In this study, we demonstrate that manipulation of BDNF expression has a reciprocal effect on STEP61 levels. Reduced BDNF signaling leads to elevation of STEP61 both in BDNF +/− mice and after acute BDNF knockdown in cortical cultures. Moreover, a newly identified STEP inhibitor reverses the biochemical and motor abnormalities in BDNF +/− mice. In contrast, increased BDNF signaling upon treatment with a tropomyosin receptor kinase B agonist results in degradation of STEP61 and a subsequent increase in the tyrosine phosphorylation of STEP substrates in cultured neurons and in mouse frontal cortex. These findings indicate that BDNF‐tropomyosin receptor kinase B signaling leads to degradation of STEP61, while decreased BDNF expression results in increased STEP61 activity. A better understanding of the opposing interaction between STEP and BDNF in normal cognitive functions and in neuropsychiatric disorders will hopefully lead to better therapeutic strategies. Altered expression of BDNF and STEP61 has been implicated in several neurological disorders. BDNF and STEP61 are known to regulate synaptic strengthening, but in opposite directions. Here, we report that reduced BDNF signaling leads to elevation of STEP61 both in BDNF +/− mice and after acute BDNF knockdown in cortical cultures. In contrast, activation of TrkB receptor results in the degradation of STEP61 and reverses hyperlocomotor activity in BDNF +/− mice. Moreover, inhibition of STEP61 by TC‐2153 is sufficient to enhance the Tyr phosphorylation of STEP substrates and also reverses hyperlocomotion in BDNF +/− mice. These findings give us a better understanding of the regulation of STEP61 by BDNF in normal cognitive functions and in neuropsychiatric disorders. Abstract : Altered expression of BDNF and STEP61 has been implicated in several neurological disorders. BDNF and STEP61 are known to regulate synaptic strengthening, but in opposite directions. Here, we report that reduced BDNF signaling leads to elevation of STEP61 both in BDNF +/− mice and after acute BDNF knockdown in cortical cultures. In contrast, activation of TrkB receptor results in the degradation of STEP61 and reverses hyperlocomotor activity in BDNF +/− mice. Moreover, inhibition of STEP61 by TC‐2153 is sufficient to enhance the Tyr phosphorylation of STEP substrates and also reverses hyperlocomotion in BDNF +/− mice. These findings give us a better understanding of the regulation of STEP61 by BDNF in normal cognitive functions and in neuropsychiatric disorders.